LEADERSHIP STYLES, INTELLIGENCE AND TACTIT KNOWLEDGE - Castro Solano, Alejandro; Benautil, Denise (Anales de Psicología / Annals of Psychology, 2007)
The present investigation had as a main goal to establish the relationship among the different profiles of leadership styles, intelligence and academic achievement of military cadets doing military training on leadership skills. Participants were 412 cadets of a military institution belonging to the Argentine Armed Forces. Most of the subjects were males (Mean = 22.13 years, SD= 2.21). The leadership styles were as-sessed by means of the questionnaire CELID. The academic achievement was evaluated by means of the academic grades. Intelligence was measured by abstract and verbal reasoning test (Differential Aptitude Test). The military achievement was evaluated by superior officers and a test of prac-tical intelligence that actually assesses tacit military knowledge (CTLM). The conclusions of the study indicate that the leaders with leadership style predominantly transformational and secondarily transactional were those that had a major capacity of abstract reasoning and that could handle unstructured situation with more tacit knowledge. Likewise they were those who had a previous trajectory of academic and military achieve-ment.